Processo de avaliação de quarta geração em um ambulatório de saúde mental : perspectiva dos profissionais - Paiano, Marcelle (2013)
The network of services in mental health care consists of several caring devices that enable the psychosocial care of patients with mental disorders. The outpatient clinic which is specialized in mental health, one of the components of this network, was the research site. The object of investigation consisted in the evaluation of mental health outpatient clinic, and the main objective is to evaluate the service from the perspective of the professionals who work in it. This is an evaluative study of qualitative approach, a case study, which used the methodological assumptions of the Fourth Generation Evaluation. The informants were 12 professionals who have worked in mental health outpatient clinic in a city in northwestern of Paraná. Data were collected in February and March of 2013 by non-participant observation(80 hours), individual open interviews and a negotiating session with the group of interest(160 hours). Data were analyzed using the Constant Comparative Method. During the trading session there was consensus among participants on some potentialities related to the host, bonding and commitment of staff, the support offered to the health care system through outpatient multidisciplinary team, and the projects undertaken and existing partnerships with other institutions to promote the social reintegration of patients. On the other hand, we have realized some aspects of the service that needs to be improved, such as the organizational structure, especially in relation to how to access physical structure and the presence of extensive waiting list for treatment. They also highlighted the ignorance that exists among professionals in general about the operation of the mental health system and the activities conducted by it, the turnover of professionals -especially physicians, deficiency in training and continuing education, and professional devaluation.As proposals for improvements to the service, the professionals believe to be necessary to rethink the process of outpatient work by redesigning the host users, investing in assistance in groups and in PrimaryCare as a gateway and still enhancing the links between the mental health services. Thus, it is concluded that the outpatient service, in the way it has been constituted, must be overcome, and it is necessary to review its functions in order to build new relationships with other network devices, to enhance the psychosocial activities, as well as investing in care model of territorial base.